Influence of Copper on А1 to L1₀ Phase Transformation in Nanoscale Fe₅₀Pt₅₀ Films - Makogon, Yu.M.; Pavlova, O.P.; Sidorenko, S.I.; Verbytska, T.I.; Verbytska, M.Yu.; Fihurna, O.V. (Металлофизика и новейшие технологии, 2015)
By the methods of materials science, the effect of intermediate Cu layer with low surface energy (≅1.83 J/m²) (top, intermediate, and underlayer) in [Fe₅₀Pt₅₀(15 nm)/intermediate Cu(7.5 nm) layer/Fe₅₀Pt₅₀ (15 nm)]n (where n=1,2), top Cu(7.5 nm) layer/Fe₅₀Pt₅₀(15 nm) and Fe₅₀Pt₅₀ (15 nm)/underlayer Cu(7.5 nm) film compositions on SiO₂(100 nm)/Si(001) substrates on diffusion phase-formation processes and L1₀ phase formation, its structure, and magnetic properties at annealing in vacuum is studied. The film compositions are prepared by magnetron sputtering on thermally oxidized SiO₂ layer by thickness of 100 nm on monocrystalline Si(001) substrate. Subsequent heat treatment is carried out at high vacuum of 1.3∙10⁻³ Pa in the 300—900°C temperature range during 30 s at each temperature. As determined, the chemically disordered A1(FePt) phase is formed in all as-deposited films. The formation of chemically ordered L1₀(FePt) phase in [Fe₅₀Pt₅₀(15 nm)/Сu(7.5 nm) intermediate layer/Fe₅₀Pt₅₀(15 nm)]n films (where n=1,2) with intermediate layers takes place during annealing at 700°C and is accompanied by sharp coercivity increase, which also rises after subsequent high-temperature annealing. In the films with top copper layer, the temperature of L1₀(FePt) phase formation rises up to 900°C. In the films with copper underlayer, the formation of L1₀(FePt) phase is not detected by X-ray analysis, but small coercivity increasing after annealing within the temperature range of 800—900°C can testify that ordering processes proceed.